2007
DOI: 10.1111/j.1600-6143.2007.01901.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Immune Tolerance to Blood Group Antigens in a Case of ABO‐Incompatible Pediatric Liver Transplantation

Abstract: In a 12-year-old patient with blood group O, who had received a partial liver graft 10 years ago from his father with blood group A, the levels of anti-A-specific antibodies (Abs) were persistently undetectable after the transplantation, while the levels of anti-B-specific Abs gradually increased and attained a plateau. Peripheral blood mononuclear cells (PBMCs) from this patient were engrafted into NOD/SCID mouse in order to investigate the immune response to donor-type blood group antigens. Even after sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In addition, assessment of B‐cell‐specific immunity is important for evaluating the potential risk of AMR. Analysis of peripheral blood B cells from stable paediatric recipients after ABOi LDLT showed that these cells were incapable of producing antibodies against donor blood‐type antigens; however, they did produce antibodies against nondonor polysaccharides [37]. Thus, these results provide evidence for immune tolerance to donor blood group antigens after ABOi LDLT.…”
Section: Other Recent Findings and Future Directionsmentioning
confidence: 99%
“…In addition, assessment of B‐cell‐specific immunity is important for evaluating the potential risk of AMR. Analysis of peripheral blood B cells from stable paediatric recipients after ABOi LDLT showed that these cells were incapable of producing antibodies against donor blood‐type antigens; however, they did produce antibodies against nondonor polysaccharides [37]. Thus, these results provide evidence for immune tolerance to donor blood group antigens after ABOi LDLT.…”
Section: Other Recent Findings and Future Directionsmentioning
confidence: 99%
“…These data suggest that anergy does not play a role in this setting, and that antigen‐specific B cells are tolerized by deletion or receptor editing . A similar tolerant state among A antigen‐specific B cells has also been observed following blood‐group A‐to‐O pediatric liver transplantation . However, it is important to note that, in this setting, almost every recipient tolerant to donor type A/B antigens was treated with CIs to prevent the T‐cell‐mediated rejection of allografts.…”
Section: B‐cell Immunitymentioning
confidence: 99%
“…45 A similar tolerant state among A Ag-specific B cells has also been observed following blood group A-to-O pediatric liver transplantation. 46 However, it is important to note that in this setting, almost every recipient tolerant to donor type A/B antigens was treated with calcineurin inhibitors to prevent T-cell-mediated rejection of allografts. Consistent with our findings that calcineurin inhibitors block segregation to CD5 ϩ B-1a cells, the proportion of B-1a cells in peripheral blood was significantly reduced in patients persistently taking either CsA or tacrolimus in our preliminary study (data not shown).…”
Section: Elimination Of B Cells Responding To Group a Carbohydrates 4571mentioning
confidence: 99%